Inhibition of TGF‐β Increases Bone Volume and Strength in a Mouse Model of Osteogenesis Imperfecta. (3rd August 2021) - Greene, Benjamin; Russo, Ryan J; Dwyer, Shannon; Malley, Katie; Roberts, Errin; Serrielo, Joseph; Piepenhagen, Peter; Cummings, Sheila; Ryan, Susan; Zarazinski, Christine; Uppuganti, Sasidhar; Bukanov, Nikolai; et al.
ABSTRACT: Osteogenesis imperfecta (OI), is a genetic disorder of bone fragility caused by mutations in collagen I or proteins involved in collagen processing. Previous studies in mice and human OI bones have shown that excessive activation of TGF‐β signaling plays an important role in dominant and recessive OI disease progression. Inhibition of TGF‐β signaling with a murine pan‐specific TGF‐β neutralizing antibody (1D11) was shown to significantly increase trabecular bone volume and long bone strength in mouse models of OI. To investigate the frequency of dosing and dose options of TGF‐β neutralizing antibody therapy, we assessed the effect of 1D11 on disease progression in a dominant OI mouse model ( col1a2 gene mutation at G610C). In comparison with OI mice treated with a control antibody, we attempted to define mechanistic effects of 1D11 measured via μCT, biomechanical, dynamic histomorphometry, and serum biomarkers of bone turnover. In addition, osteoblast and osteoclast numbers in histological bone sections were assessed to better understand the mechanism of action of the 1D11 antibody in OI. Here we show that 1D11 treatment resulted in both dose and frequency dependency, increases in trabecular bone volume fraction and ultimate force in lumbar bone, and ultimate force, bending strength, yield force, and yield strength in the femur ( p  ≤ 0.05). Suppression of serum biomarkers of osteoblast differentiation, osteocalcin, resorption, CTx‐1, and bone formation were observed after 1D11 treatment of OI mice. Immunohistochemical analysis showed dose and frequency dependent decreases in runt‐related transcription factor, and increase in alkaline phosphatase in lumbar bone sections. In addition, a significant decrease in TRACP and the number of osteoclasts to bone surface area was observed with 1D11 treatment. Our results show that inhibition of the TGF‐β pathway corrects the high‐turnover aspects of bone disease and improves biomechanical properties of OI mice. These results highlight the potential for a novel treatment for osteogenesis imperfecta. © 2021 Sanofi‐Genzyme. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.